A Single Low Dose of Dexmedetomidine Efficiently Attenuates Esketamine-Induced Overactive Behaviors and Neuronal Hyperactivities in Mice - Chu, Qinjun; Zhu, Kuicheng; Bai, Yafan; Shang, Huijie; Zhang, Dongqing; Zhao, Mingming; Zheng, Ping; Jin, Xiaogao (Frontiers in Human Neuroscience, 2021)
Introduction Esketamine (S(+)-ketamine) is now used as an alternative to its racemic mixture---ketamine in anesthesia. Esketamine demonstrated more powerful potency and rapid recovery in anesthesia, and less psychotomimetic side effects comparing with ketamine. But esketamine could still induce psychological side effects in patients. This study was to investigate whether dexmedetomidine can attenuate the esketamine-induced neurotoxicity in Kunming mice. Methods Dexmedetomidine 0.25, 0.5, and 1mg/kg acompanied with esketamine 50mg/kg were administrated on Kunming mice to assess the anesthesia quality for 1 hour. The indicators, such as time to action, duration of agitatiton, duration of ataxia, duration of loss pedal withdrawal reaction, duration of catalepsy, duration of right reflex loss, duration of sedation, were recorded for 1 hour after intraperitoneal administration. The c-Fos expression in brain was detected by immunohistochemistry and Western Blot after 1h administration. Consideraing the length of recovery time more than 1 hour in dexmedetomidine and dexmedetomidine with esketamine groups, another mice were repeatly used to evaluate recovery time from the administration to the complete recovery. Results Dexmedetomidine dose-dependently increased recovery time when administrated with esketamine or alone. Dexmedetomidine combined with esketamine efficiently attenuated duration of agitation, ataxia, and catalepsy. Dexmedetomidine synergically improved the anesthesia of esketamine by increasing duration of sedation, loss of righting reflex, and loss of pedal withdrawal reaction. Esketamine induced high expression of c-Fos in cerebral cortex, hippocampus, thalamus, amygdala, hypothalamus, and cerebellum 1 hour after administration. Wester Blot results indicated that dexmedetomidine at doses of 0.25, 0.5, and 1mg/kg all could significantly alleviated the esketamine-induced c-Fos expression in the mice brain. Conclusion Dexmedetomidine ranged from 0.25mg/kg to 1mg/kg all could improve the anesthesia quality and deceased the neurotoxicity and the overactive behaviours when combined with esketamine. However, dexmedetomidine does-dependently increased the recovery time from anesthesia. It demonstrated that a small dose of dexmedetomine 0.25mg/kg could be sufficient to attenuate esketamine-induced psychotomimetic side effects without extension of recovery time in Kunming mice.